Do male sticklebacks use visual and/or olfactory cues to assess a potential mate’s history with predation risk? - Dellinger, Marion (Anim Behav, 2018)
Differential allocation occurs when individuals alter their reproductive investment based on their mate’s traits. A previous study showed that male threespine sticklebacks, Gasterosteus aculeatus, reduced courtship towards females that had previously been exposed to predation risk compared to unexposed females. This suggests that males can detect a female’s previous history with predation risk, but the mechanisms by which males assess a female’s history are unknown. To determine whether males use chemical and/or visual cues to detect a female’s previous history with predation risk, we compared rates of courtship behaviour in the presence of visual and/or olfactory cues of predator-exposed females versus unexposed females in a 2×2 factorial design. We found that males differentiate between unexposed and predator-exposed females using visual cues: regardless of the olfactory cues present, males performed fewer zigzags (a conspicuous courtship behaviour) when they were exposed to visual cues from predator-exposed females compared to unexposed females. However, males’ response to olfactory cues changed over the course of the experiment: initially, males performed fewer courtship displays when they received olfactory cues of predator-exposed females compared to unexposed females, but they did not discriminate between cues from predator-exposed and unexposed females later in the experiment. A follow-up experiment found that levels of cortisol released by both predator-exposed and unexposed females decreased over the course of the experiment. If cortisol is linked to or correlated with olfactory cues of predation risk that are released by females, then this suggests that the olfactory cues became less potent over the course of the experiment. Altogether, these results suggest that males use both visual and olfactory cues to differentiate between unexposed and predator-exposed females, which may help ensure reliable communication in a noisy environment.